PERBANDINGAN ALGORITMA DIJKSTRA DAN ALGORITMA ANT COLONY DALAM PENENTUAN JALUR TRANSPORTASI UMUM - Kadim, Ahmad Azhar; Sunardi, Sunardi; Yudhana, Anton (Jurnal Sistem Komputer, 2020)
The purpose of this research is to compare the working principle and characteristics between Dijkstra algorithm and Ant Colony Optimization in determining the shortest path Dijkstra algorithm requires weight to determine the shortest path, without the weight of Dijkstra, algorithm cannot run , while Ant Colony Optimization algorithm does not require weight at run because on the working principle of this algorithm will produce the output or weight when the ant finishes the journey . Therefore, this algorithm consume more RAM and takes a long time of execution when run than Dijkstra algorithm. The Dijkstra algorithm got the fastest result 0.0045 seconds while on algorithm Ant Colony Optimization 0.0126 sec, for RAM usage result obtained by Dijsktra algorithm stable 387.14 kb different from ACO obtained results vary with the smallest result is 712.42 kb The equation of both of these algorithms are the output path and the resulting distance are the same so that it can be implemented for the determination of public transportation routes. The application of this research will be applied to Transjogja which is one of the public transportations in Yogyakarta.